ECOLOGICALLY SAFE BENZIMIDAZOLE-BASED ANTHELMINTIC DRUGS: SYNTHESIS, PROPERTIES, MEDICATION - S. S. Khalikov; I. A. Arkhipov; A. I. Varlamova; Marat S. Khalikov; Yu. S. Chistyachenko; A. V. Dushkin (Юг России: экология, развитие)
The aim is to study the process of mechanochemical modification of the physico-chemical and anthelmintic benzimidazole properties of drugs to change their water solubility and increase their efficiency.Methods. We have used the technology of solid phase mechanical processing of substances with polysaccharides to obtain the supramolecular complexes, which are characterized by a complex of physico-chemical methods (IR spectroscopy, DTA, XRF, solubility, etc.) as well as tested for anthelmintic effect in laboratory models and experiments on sheep.Results. The drug has a high efficiency in laboratory models of helminthes and in experiments on sheep infested spontaneously with nematodes of gastrointestinal tract lowering the dosages of substance.Conclusion. Solid phase mechanochemical processing of certain substances of benzimidazole anthelmintic drugs with polysaccharides shows the possibility of obtaining environmentally friendly products with improved solubility, bioavailability and increased biological activity against nematodes.